2016
DOI: 10.1108/imds-09-2015-0405
|View full text |Cite
|
Sign up to set email alerts
|

Relating open innovation, innovation and management systems integration

Abstract: Findings: The level of IMS positively influences process and product IC. Moreover, external cooperation, and using it a high extent not only positively moderate the effects of the level of IMS over process IC, but also of process over product IC, where it becomes indispensable for its effect to be positive. Finally, investing in external knowledge is a positive moderator of the effects of the level of IMS over both: process and product IC.Originality / Value: This is one the first studies on empirically findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…This argument has led IMS to be acknowledged as a relevant sustainable management approach (Gianni et al, 2017;Jørgensen, 2008;Mustapha et al, 2017;Rebelo et al, 2016;Siva et al, 2016). As such, IMS has been positively related to innovations in general based on theoretical frameworks (Bernardo, 2014) and empirical statistical evidence (Hernandez-Vivanco et al, 2016;Simon and Petnji Yaya, 2012). However, how IMS is related to sustainable innovation (rather that innovation in general) remains a major research gap (del Río et al, 2016;Nunhes et al, 2016;Ramos et al, 2018), which will be explored in this article.…”
Section: Introductionmentioning
confidence: 98%
“…This argument has led IMS to be acknowledged as a relevant sustainable management approach (Gianni et al, 2017;Jørgensen, 2008;Mustapha et al, 2017;Rebelo et al, 2016;Siva et al, 2016). As such, IMS has been positively related to innovations in general based on theoretical frameworks (Bernardo, 2014) and empirical statistical evidence (Hernandez-Vivanco et al, 2016;Simon and Petnji Yaya, 2012). However, how IMS is related to sustainable innovation (rather that innovation in general) remains a major research gap (del Río et al, 2016;Nunhes et al, 2016;Ramos et al, 2018), which will be explored in this article.…”
Section: Introductionmentioning
confidence: 98%
“…Related to the future sustainability, discussion about internalization of MSs is also increasing in relation to IMS, as more analyses are needed to demonstrate if organizations are implementing appropriately the IMS (Heras-Saizarbitoria and Boiral, 2013;Samy et al, 2015). Finally, Hernandez-Vivanco et al (2016) found that organizations with fully IMS are more innovative (see also Simon and Yaya, 2012;Bernardo, 2014). As a summary of the research done on IMS, table 1 summarizes the qualitative studies published, as the current paper is also qualitative.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations that operate quality management systems are very successful in open innovation. Whether it is any quality management system, such an operating standard or a quality philosophy, its users are committed to continuous improvement of quality and to the satisfaction of customer demands [5,6]. However, it is not clear which quality management system is more conducive to open innovation: one that, driven by leadership, creates a quality culture and understanding of the importance of a quality philosophy to its employees; or one that specifies the quality development steps and the methods involved as a standard.…”
Section: Introductionmentioning
confidence: 99%